Overweight in family members of probands with ADHD - Geuijen, Pauline M. (Eur Child Adolesc Psychiatry, 2019)
The widely reported association between ADHD and overweight may be attributable to genetic and environmental factors also present in unaffected family members. Therefore, the purpose of this study was to examine the association between ADHD and overweight within families. A cohort was used of families with at least one member with ADHD, recruited as part of the Dutch node of the International Multicenter ADHD Genetics (IMAGE) study, with assessments taking place between 2003 and 2006, 2009 and 2012, and 2013 and 2015. The three assessment waves yielded N = 1828 youth assessments and N = 998 parent assessments from N = 447 unique families. Overweight was defined as a body mass index (BMI) ≥ 85th percentile for youth of the same age and sex; overweight in adults as a BMI ≥ 25. Effects of age, gender, and medication use (psychostimulants, antipsychotics, and melatonin) were taken into account. Generalized estimation equations were used to correct for within-family and within-subject correlations. There was no difference in risk between ADHD-affected youth and their unaffected siblings (OR 0.92, 95% CI 0.78–1.09). However, compared to population prevalence data, all ADHD family members alike were at increased risk for being overweight: ADHD-affected youth (OR 1.33, 95% CI 1.13–1.59), unaffected siblings (OR 1.73, 95% CI 1.45–2.08), mothers (OR 1.74, 95% CI 1.40–2.17) and fathers (OR 1.78, 95% CI 1.46–2.15). Parental overweight—but not parental ADHD—was predictive of offspring overweight (mothers OR 1.40; 95% CI 1.14–1.73, fathers OR 1.83; 95% CI 1.41–2.36). Being overweight runs in ADHD families, yet is not specifically linked to ADHD within families. Shared unhealthy lifestyle factors (including nutrition, sleep, exercise, stress) as well as genetic factors shared by family members likely explain the findings. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00787-019-01331-7) contains supplementary material, which is available to authorized users.